Nowadays problems with transport enterprise wastes utilization - Солошич, І. О.; Напхоненко, Н. В. (Man and Environment. Issues of Neoecology, 1970)
The analysis of waste utilization is carried out on the example of transport enterprise. The methods of improvement of transport wastes care system are assessed. The methods of regulation of wastes care process are offered.